Once upon a proverb : old and new tales shaped by proverbs - Tóthné Litovkina, Anna; Lindahl, Carl; Sidyakova, Anastasya; Fedoszov, Júlia ([A. T. Litovkina], 2004)
A collection of fabulous classic tales, fables, and stories retold with proverbs by students who have attended Anna T. Litovkina's course on Anglo-American proverbs. All 192 proverbs are listed in alphabetical order at the end of the book together with brief explanations of their meanings.
Keywords: sananlaskut; ordspråk